Hermeneutika Praksis Liberatif Farid Esack - Iswahyudi, Iswahyudi (Program Studi Studi Agama-Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2012)
The history of prophecy in general and the existence of Prophet Mohammad in particular are the evidence of the important role of Islam as religion of liberation. It means that Islam intends to pose human position into precise site, the caliphate. Muhammad Iqbal states this position as co-cretio of God. Furthermore, revelation of the Quran, according to Farid Esack, is progressive revelation. Quran is a scripture of liberation. Even though, this spirit is often arrested in the interpretations of Quran. These interpretations are often constructed only for the interest of power or the pursuit of elite. Therefore, spirit of Quranic liberation misses its strength and vitality. At this point, Farid Esack gives his attention and his intellectual concern. The weakness of Quranic interpretation inspires Farid Esack to formulate methodology of Quranic interpretation. Esack named this methodology as “liberative hermeneutics”. Esack focuses to humanize human, based on (criticizing) power system and structure of South Africa. Farid Esack gives a strong foothold to his hermeneutic theory on theological system. The choice built by him is very precise. Esack’s excess compared to other intellectual such as Arkoun and Fazlur Rahman is that Esack involves in the act of liberation and the intensity of the dialectic in the field with people of other faiths and ethnic groups and races